2021
DOI: 10.1016/j.heliyon.2021.e08026
|View full text |Cite
|
Sign up to set email alerts
|

A bifactor structural model of the Hungarian Pain Catastrophizing Scale and latent classes of a clinical sample

Abstract: Pain catastrophizing is an exaggerated cognitive-affective response to actual or anticipated pain, usually measured by the Pain Catastrophizing Scale (PCS). Our study aimed to test the bifactor measurement model of the Hungarian PCS and to identify a catastrophizing risk group with a clinically meaningful cut-off score.The data of 404 chronic spine-related (neck, back and low-back) pain patients (mean age: 58.61 (SD ¼ 14.34)) were used in our cross-sectional study. Besides pain-related and demographic data, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…23,39 However, one item (item12) showed crossloading in the three factors, being a 12-item scale different compared with the validated version in Spanish population 15,16 with a 13-item version and with the original scale with a 14-item version. 22,38 Despite the threedimensional scale structure shown in the present study, some studies have found a bi-dimensional model for this questionnaire, 24,40 and the differences between different models of the questionnaire have been studied due to the problem of the questionnaire to discriminating distinctions about factors. 41 Values for internal consistency were excellent, ranging from 0.91 to 0.92 42 for each of the factors.…”
Section: Discussionmentioning
confidence: 60%
“…23,39 However, one item (item12) showed crossloading in the three factors, being a 12-item scale different compared with the validated version in Spanish population 15,16 with a 13-item version and with the original scale with a 14-item version. 22,38 Despite the threedimensional scale structure shown in the present study, some studies have found a bi-dimensional model for this questionnaire, 24,40 and the differences between different models of the questionnaire have been studied due to the problem of the questionnaire to discriminating distinctions about factors. 41 Values for internal consistency were excellent, ranging from 0.91 to 0.92 42 for each of the factors.…”
Section: Discussionmentioning
confidence: 60%
“…Higher scores indicate a higher level of pain catastrophizing. The Hungarian version of PCS 34 , has demonstrated good internal consistency.…”
Section: Pain Catastrophizing Scalementioning
confidence: 97%
“…Endometriosis is a chronic, progressive, in ammatory gynecological disease that affects more than 70 million women worldwide. In the United States 11% of women and approximately every 10th woman worldwide and in Hungary suffer from endometriosis 34 . Additionally, it occurs among 40-50% of women with pelvic pain, 20% of women with infertility, 50% and 70% of women suffering from dysmenorrhea and dyspareunia 5 6 .…”
Section: Introductionmentioning
confidence: 99%